Perkembangan Kajian Pendidikan Karakter Religius: Analisis Jurnal Bilbiometrik pada Database Scopus - Thriska Afifandasari; Suluri Suluri; Syahrul Ramadhan (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
This study aims to analyze religious character education using bibliometric analysis on the Scopus database. Bilbiometric analysis is a popular method for analyzing scientific data. This article discusses religious character education which is concretely based on the values of the teachings of each religion and the implementation of religious character education that can be carried out in schools, families and communities synergistically in shaping the religious character of students and in this article uses bilbiometric analysis which uses Scopus indexed journal on the development of religious character education studies: Bilbiometric analysis on the Scopus database. The purpose of the bilbiometric analysis in this study was to find out the top 5 year developments related to the development of religious character education studies. Specifically, this article aims to find out the development of religious character education literature from 2018 to 2022, major journals, authors, affiliates, countries and documents in the field of character education, trending topics related to religious character education, classifications and future character education topics that will provide more research opportunities. Data collected from the Scopus database using the keyword